2014
DOI: 10.1021/am5032105
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of a High-k Dielectric on MoS2 Using Trimethylaluminum and Ozone

Abstract: We present an Al2O3 dielectric layer on molybdenum disulfide (MoS2), deposited using atomic layer deposition (ALD) with ozone/trimethylaluminum (TMA) and water/TMA as precursors. The results of atomic force microscopy and low-energy ion scattering spectroscopy show that using TMA and ozone as precursors leads to the formation of uniform Al2O3 layers, in contrast to the incomplete coverage we observe when using TMA/H2O as precursors. Our Raman and X-ray photoelectron spectroscopy measurements indicate minimal v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
112
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(131 citation statements)
references
References 31 publications
(74 reference statements)
17
112
2
Order By: Relevance
“…Thus, the top surface consists of the WS2 crystal basal planes and grain boundaries. It has been observed that the crystal basal planes of 2D materials typically have a low reactivity for ALD [36][37][38] . Instead, the chemisorption of ALD precursors on 2D materials can occur at line defects and grain boundaries 38 .…”
Section: A Substrate Enhanced Growth Of Ws2 Peald On Amorphous Al2o3mentioning
confidence: 99%
“…Thus, the top surface consists of the WS2 crystal basal planes and grain boundaries. It has been observed that the crystal basal planes of 2D materials typically have a low reactivity for ALD [36][37][38] . Instead, the chemisorption of ALD precursors on 2D materials can occur at line defects and grain boundaries 38 .…”
Section: A Substrate Enhanced Growth Of Ws2 Peald On Amorphous Al2o3mentioning
confidence: 99%
“…It inherits all the fundamental fabrication challenges of a TFET including doping profile, alignment especially gate registry, gate dielectrics, ohmic contacts. Atomic layer deposition has been improved over years to achieve good quality gate dielectrics on 2D crystals [32]. Using 2D dielectrics such as hexagonal boron nitride as the gate dielectrics has also been pursued [33].…”
Section: E Experimental Insightsmentioning
confidence: 99%
“…Each MoS 2 TFT channel was defined by photolithography and dry-etching (O 2 plasma treatment) isolation process [the detailed APCVD process flow and material properties of the transferred and isolated MoS 2 thin film are shown in Figure S1 (Supporting Information), which includes the Raman spectra and atomic force microscopy (AFM) profile]. [30,[45][46][47] During the fabrication process, via holes through the Al 2 O 3 GI layer, defined by photolithography and wet-etching process using buffered oxide etchant (BOE), were formed to connect the source electrode of the switching TFT and gate electrode of the driving TFT. [30] For the source/drain electrode, Ti/Au was employed for ohmic contact to the MoS 2 active layer.…”
mentioning
confidence: 99%